Global Christianity contested claims - Wijsen, Frans Jozef Servaas, 1956-; Schreiter, Robert J. (Amsterdam ; New York, NY : Rodopi, 2007)
In 2002 Philip Jenkins wrote The Next Christendom . Over the past half century the centre of gravity of the Christian world has moved decisively to the global South, says Jenkins. Within a few decades European and Euro-American Christians will have become a small fragment of world Christianity. By that time Christianity in Europe and North America will to a large extent consist of Southern-derived immigrant communities. Southern churches will fulfil neither the Liberation Dream nor the Conservative Dream of the North, but will seek their own solutions to their particular problems. Jenkins' boo
Introduction / Frans Wijsen -- Christianity moves South / Philip Jenkins -- Global Christianity, new empire, and old Europe / Werner Ustorf -- Christian enculturation in the two-thirds world / Ben Knighton -- The future shape of Christianity from an Asian perspective / Sebastian C.H. Kim -- Jenkins' The Next Christendom and Europe / Frans J. Verstraelen -- Challenges to the next Christendom: Islam in Africa / John Chesworth -- Realistic perspectives for the Christian diaspora of Asia / Karel Steenbrink -- Religion in the Caribbean: creation by Creolisation / Joop Vernooij -- Pentecostal conversion careers in Latin America / Henri Gooren -- Theologies of Anowa's daughters: an African women's discourse / Martha Frederiks -- Filipina domestic workers in Hong Kong / Gemma Cruz-Chia -- Epilogue / Robert Schreiter.
"It is the outcome of an international conference on southern Christianity and its relation to Christianity in the north, held in the conference centre of Radboud University Nijmegen, the Netherlands."--P. [4] of cover.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Christianity -- Forecasting -- Congresses; Jenkins, Philip, -- 1952- -- Criticism, textual -- Congresses; RELIGION -- Christianity -- General; RELIGION -- Christian Theology -- Systematic; Electronic books